2019
DOI: 10.1021/acsaem.9b01219
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin MoS2 Nanosheets Vertically Grown on CoS2 Acicular Nanorod Arrays: A Synergistic Three-Dimensional Shell/Core Heterostructure for High-Efficiency Hydrogen Evolution at Full pH

Abstract: A three-dimensional (3D) MoS2/CoS2 composite with shell/core heterostructure is in situ synthesized, which is composed of CoS2 acicular nanorod arrays and edge-terminated MoS2 nanosheets vertically grown on each CoS2 nanorod. Benefiting from the epitaxial growth of 2H-MoS2 on the surface of CoS2, the edge planes of ultrathin MoS2 nanosheets are significantly exposed. Due to the structural properties, a large number of direct contact areas are formed between MoS2 and CoS2, and a strong interaction between these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 67 publications
(90 reference statements)
1
34
0
Order By: Relevance
“…As shown in Fig. 5b, the 61 and CoS 2 -C@MoS 2 nano-bers (61 mV dec À1 ). 62 The small Tafel slope of 3D ower-like CoS 2 /MoS 2 HNSAs unveils a fast increase of hydrogen generation rate with increasing applied overpotential.…”
Section: Resultsmentioning
confidence: 70%
“…As shown in Fig. 5b, the 61 and CoS 2 -C@MoS 2 nano-bers (61 mV dec À1 ). 62 The small Tafel slope of 3D ower-like CoS 2 /MoS 2 HNSAs unveils a fast increase of hydrogen generation rate with increasing applied overpotential.…”
Section: Resultsmentioning
confidence: 70%
“…The unique vertical growth morphology was conducive to achieving maximum exposure of the active sites. Huang et al [195] used the advantageous vertical growth method to prepare MoS2/CoS2 catalysts. The heterojunction catalyst RGO/MoS2/PD was prepared by Pandey et al [196]; during the heterojunction formation process, a phase transition was observed.…”
Section: Formation Of Heterostructurementioning
confidence: 99%
“…Similarly, the vertically aligned 3D core/shell structures of MoS 2 on CoS 2 were grown to check their electrochemical performance; an improved performance of HER was observed. The surface morphology and electrochemical activity curves of these are shown in Figure b,c …”
Section: Applications Of Mos2 For Energy Conversion and Storagementioning
confidence: 99%
“…b) SEM image of MoS 2 /CoS 2 . c) Electrochemical hydrogen evolution of various electrodes at 5 mV s −1 in 1 m KOH, Reproduced with permission . Copyright 2019, American Chemical Society.…”
Section: Applications Of Mos2 For Energy Conversion and Storagementioning
confidence: 99%